(untitled) (Revista Direito em Debate, 2022)
The theme of this article is personality rights, with special emphasis on the right to privacy, in the context of the information society and surveillance. The objective was to analyze which of the personality rights was the most directly affected by the new technologies (NT) and by the information and communication technologies (ICT), the new problems that were added to such rights, as well as the possibility or not of a tutelage transversal (at national and international level, and of vertical and complementary dimensions). As a result, it was found that, in particular, the right to privacy was the most affected. It is concluded that the internet is just a space where fundamental rights will perform the same function that they have always played historically, however, this new space has given rise to new demands generated by globalization, increasing the speed and the way of connection of events, thus appearing the need for transversal protection of privacy, at national and international level, and vertical and complementary dimensions. This article is a theoretical study. Theoretical approaches and applied research are used in approximation with other fields of scientific knowledge such as computer science, among others. The research is based on hypothetical-deductive reasoning. The research will be bibliographic and documentary, in which an exact understanding will be sought through materials such as laws, official websites and legal doctrine, national and international, applicable to the theme.